Association between mean arterial pressure and risk of type 2 diabetes mellitus: The Rural Chinese Cohort Study. Issue 5 (October 2020) - Guo, Chunmei; Qin, Pei; Li, Quanman; Zhang, Dongdong; Tian, Gang; Liu, Dechen; Liu, Leilei; Cheng, Cheng; Chen, Xu; Qie, Ranran; Han, Minghui; Huang, Shengbing; et al.
Highlights: The study explored the association between mean arterial pressure and T2DM. A large sample size in rural Chinese people. Restricted cubic spline models were used to evaluate the dose–response association. Subgroup and sensitivity analyses were also performed. Abstract: Aims: Limited evidence is available on the association of mean arterial pressure and risk of type 2 diabetes mellitus (T2DM) among Chinese people. We aimed to investigate the association between MAP and risk of T2DM in rural Chinese adults. Methods: We performed a cohort study of 12, 284 eligible participants (4668 men and 7616 women) without T2DM at baseline. Cox proportional-hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for the association of MAP with risk of T2DM. Restricted cubic spline models were used to evaluate the dose–response association between MAP and risk of T2DM. Results: During a median of 6.01 years follow-up (73, 403.52 person-years), T2DM developed in 847 participants (318 men and 529 women). In the multivariable-adjusted models, risk of T2DM was significantly higher for women with the third (90−100 mmHg) and fourth MAP categories (≥100 mmHg) than the first category (<80 mmHg) after adjusting for confounders (HR = 1.74 [95% CI 1.14–2.68] and 1.84 [1.20–2.83]). Restricted cubic spline analysis revealed increased risk of T2DM with increasing MAP for women. Conclusion: High MAP was related to high incident T2DM among women in China.